Exploring impacts of process technology development and regional factors on life cycle greenhouse gas emissions of corn stover ethanol. (April 2015) - McKechnie, Jon; Pourbafrani, Mohammad; Saville, Bradley A.; MacLean, Heather L.
Abstract: This paper examines impacts of regional factors affecting biomass and process input supply chains and ongoing technology development on the life cycle greenhouse gas (GHG) emissions of ethanol production from corn stover in the U.S. Corn stover supply results in GHG emissions from −6 gCO2 eq./MJ ethanol (Macon County, Missouri) to 13 gCO2 eq./MJ ethanol (Hardin County, Iowa), reflecting location-specific soil carbon and N2 O emissions responses to stover removal. Biorefinery emissions based on the 2011 National Renewable Energy Laboratory (NREL) process model are the single greatest emissions source (18 gCO2 eq./MJ ethanol) and are approximately double those assessed for the 2002 NREL design model, due primarily to the inclusion of GHG-intensive inputs (caustic, ammonia, glucose). Energy demands of on-site enzyme production included in the 2011 design contribute to reducing the electricity co-product and associated emissions credit, which is also dependent on the GHG-intensity of regional electricity supply. Life cycle emissions vary between 1.5 and 22 gCO2 eq./MJ ethanol (2011 design) depending on production location (98%–77% reduction vs. gasoline). Using system expansion for co-product allocation, ethanol production in studied locations meet the Energy Independence and Security Act emissions requirements for cellulosic biofuels; however, regional factors and on-going technology developments significantly influence these results. Highlights: Regional parameters and technology development impact life cycle greenhouse gas emissions of corn stover-derived ethanol. The impacts of corn stover removal on soil carbon stocks and N2 O emissions are the dominant regionally-dependent parameters. Greenhouse gas-intensive inputs (caustic, ammonia, glucose) double biorefinery emissions (2011 vs 2002 NREL design models). All ethanol pathways meet US EISA emissions reduction threshold when system expansion is used for co-product allocation.